(untitled) (Revista Ciência Agronômica, 2015)
The importance in folk medicine, combined to threats in their environment, becomes necessary to carry out studies involving large-scale propagation of Lippia genus. Although the tissue culture propagation is widely disseminated for medicinal plants, for L. rotundifolia any article was published yet. The present study aimed to establish an efficient protocol for micropropagation of L. rotundifolia. Nodal segments, taken from plants collected in the Espinhaço Range, were disinfected, and cultures were initiated on MS medium with PVPP (1 g L- 1), sucrose (3%) and agar (0.7%). The culture were maintained in a growth room at controlled conditions. Disinfestation procedures and the supply of PVPP on culture media resulted in both reduced contamination and phenol oxidation rates, with more than 90% of viable cultures. In the multiplication phase were tried different BAP and NAA combinations supplied to the MS medium. The treatment that resulted in highest multiplication rates was 0.33 ȝM BAP. The effects of NAA were evaluated for in vitro rooting. At 0.44 ȝM, rooting was 70% higher than that observed in the control. The acclimatization was held in trays with substrate, coated with translucent plastic and kept under shade. The plantlets were transferred to the greenhouse after 15 days and transplanted to plant beds after 30 days. The acclimatized plantlets bloomed one year after the transference to field conditions, showing that the in vitro culture did not affect the vegetative and reproductive development, which confirms the potential of micropropagation to reduce the extinction risk of L. rotundifolia.